Assessing the wavefront aberrations of the emmetropic eye after a reading task - Franco, Sandra (2017)
The main goal of this study was to investigate the effect of performing a near task on eye's optical quality.Wavefront aberrations data of 35 young emmetropic eyes were measured with the L80 Wave+: (1) ocular aberrations were measured with the wavefront sensor, (2) corneal wavefront aberrations were computed from the Placido disk system's data and (3) the internal wavefront component of the eye were determined as the difference between ocular and corneal wavefront aberrations. The measurements were performed before and after a reading task was completed.Several corneal and internal aberration terms changed in opposite directions with the reading task, most of them changing its sign relative to the pre-task condition. The opposite sign between the cornea and the internal optics produced a partial balance that leaved the eye with less aberrations than the individual components. Furthermore, the optical quality of the eye and the retinal image quality changes with a reading task.Overall optical quality of the eye and its components reduced with the near task, as a consequence of the increase in wavefront aberrations after the reading. The reading task induced a myopic shift of 0.18 D in the distance M value of the emmetropic subjects.